232k views
4 votes
7(x - 2) = 3(x + 4)

Solve the following equation. Then enter your answer in the space provided using mixed number format.

User Jfenwick
by
6.0k points

2 Answers

3 votes

For this case we must solve the following equation:


7 (x-2) = 3 (x + 4)

Applying distributive property to the terms within the parenthesis we have:


7x-14 = 3x + 12

We subtract 3x on both sides of the equation:


7x-3x-14 = 12\\4x-14 = 12

Adding 14 to both sides of the equation:


4x = 12 + 14\\4x = 26

Dividing between 4 on both sides of the equation:


x = \frac {26} {4} = \frac {13} {2}

ANswer:


x = \frac {13} {2}\\x = 6 \frac {1} {2}

User Christy
by
5.2k points
2 votes

Answer:

In mixed number format: 6 1/2

Explanation:

To solve the following equation: 7(x - 2) = 3(x + 4), first we need to apply the distributive property:

7(x - 2) = 3(x + 4) → 7x -14 = 3x + 12

Solving for 'x' → 4x = 26 → x = 6.5

→ In mixed number format: 6 1/2

User Ben In CA
by
5.0k points